Congenital toxoplasmosis in early childhood and toxoplasmosis in women of reproductive age in Colombia according to the integral system of social protection - Pedraza López, Geraldine; Otálora , Paula Alexandra; Vargas Torres, Ludy Alexandra (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2023)
Introduction: congenital toxoplasmosis is the result of mother-to-child transmission of T. gondii, which is preventable and should be monitored in maternal and child health. Objective: to determine the prevalence of congenital toxoplasmosis in Colombia based on data from the Individual Health Provision Records of children under 5 years of age and women of reproductive age. Methods: descriptive study using data available in the Comprehensive Social Protection Information System of the Ministry of Health, during the years 2015 to 2020. Results: during January 1, 2015 and December 31, 2020, a prevalence of congenital Toxoplasmosis was estimated at 0.4 per 1,000 children and prevalence of Toxoplasmosis at 2 per 1,000 women of reproductive age. The highest reported cases were found in the department of Huila. Conclusion: the estimated prevalence was low in comparison with other primary sources, being the behavior of these events heterogeneous among departments. There is a need for continuous monitoring of these diagnoses in each territory and adequate recording of the purpose of the consultation to facilitate the evaluation of the behavior of these events in susceptible populations such as pregnant women.